International Students Friendly Library - Are We There Yet. - Mohamad, Radia Banu Jan; Napiah, Mohd Kamal Mohd; Jaafar, Cik Ramlah Che (2012)
The number of international students attending universities in Malaysia particularly Universiti Sains Malaysia has been increasing steadily in recent years. This trend poses a challenge to the academic library in providing a high quality information services to meet the needs and expectations of students.